Dialektika dalam Reformulasi Kriteria Rukyatul Hilal: Dari Rukyat Mutlak hingga QRNU - Hijriyati, Muthi'ah; Lusdiyanto, Karis (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
Nahdlatul Ulama' as a representative of a community organization that views rukyah as the basis for determining the start of the month is often faced with hisab. However, history records that the NU’s ijtihad process moved dynamically and did not reject hisab. Starting from using rukyah absolutely, then hisab is used as a "partner" and the basis for implementing rukyah, until hisab is positioned to also thwart istimal norms in the position of qath'i al-rukyah. This developing formulation is interesting to study in the context of dialectics initiated by Hegel. Hegel's philosophical concept will be applied to explore the dynamics of shifts in NU's thinking in its ijtihad regarding the determination of the beginning of the month in Indonesia. This type of research is qualitative with a library research approach by collecting data from various written sources. This data will then be processed in a descriptive-analytical methods and produce an understanding that the formulation of rukyatul hilal in NU in the early days was to use pure rukyah based on an understanding of the hadith text of the prophet Muhammad saw. This is a thesis that confronts the antithesis of the developing condition of science, where humans have been able to calculate and predict the occurrence of conjunctions and are supported by astronomical data. This process of dialogue and thesis-antithesis conflict presents a result of ijtihad in the form of the concept of NU qath'i al-rukyah which is a synthesis in the struggle for NU thought. It is possible that new thoughts will emerge in the future as evidence that the dialectical process is still and will continue to run in the scientific treasures of Nahdlatul 'Ulama